Some geometric properties of a new modular space defined by Zweier operator - Et, Mikail; Karakas, Murat; Cinar, Muhammed (Springer International Publishing Ag, 2013)
In this paper, we define the modular space by using the Zweier operator and a modular. Then, we consider it equipped with the Luxemburg norm and also examine the uniform Opial property and property beta. Finally, we show that this space has the fixed point property. MSC: 40A05, 46A45, 46B20.
Keywords: Zweier operator; Luxemburg norm; modular space; uniform Opial property; property (beta)